2009
DOI: 10.1215/10642684-2008-020
|View full text |Cite
|
Sign up to set email alerts
|

Situating “FLUIDITY”

Abstract: Drawing on Butler's theory of gender performativity, which conceptualizes the discursive production of the gendered subject and the corresponding “constitutive instabilities” of such reiterative practices, I provide an empirical sociological examination of how individuals negotiate potentially unintelligible identities in their daily lives and the extent to which these practices call into question the conceptual dichotomization of stability and fluidity. While transsexed bodies, histories, and identities may “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 30 publications
2
49
0
3
Order By: Relevance
“…Rather, Davis (2009, 99 -100) rightly suggests that 'gender identity is not static, but it is also not unbounded -neither for trans people nor for everyone else'. Recent work on trans identity formations by scholars such as Valentine (2007) and Davis (2009), which is guided by empirical research, also illustrates the importance of developing an intersectional analysis of transgender that keeps a critical eye on how the category of 'transgender' is cut through with variables of 'race', ethnicity, geographical location, sexuality and age -as well as distinct (trans) gendered positionings. 6 Building on intersectional theory developed by black feminist scholars and activists (see hooks 1984), feminist writers have employed the notion of intersectionality to examine the ways in which forms of inequality interrelate (Crenshaw 1989).…”
Section: Queering Binariesmentioning
confidence: 99%
“…Rather, Davis (2009, 99 -100) rightly suggests that 'gender identity is not static, but it is also not unbounded -neither for trans people nor for everyone else'. Recent work on trans identity formations by scholars such as Valentine (2007) and Davis (2009), which is guided by empirical research, also illustrates the importance of developing an intersectional analysis of transgender that keeps a critical eye on how the category of 'transgender' is cut through with variables of 'race', ethnicity, geographical location, sexuality and age -as well as distinct (trans) gendered positionings. 6 Building on intersectional theory developed by black feminist scholars and activists (see hooks 1984), feminist writers have employed the notion of intersectionality to examine the ways in which forms of inequality interrelate (Crenshaw 1989).…”
Section: Queering Binariesmentioning
confidence: 99%
“…(Cornell, 2010, p. 32; see also Deutsch, 2007;Risman, 2009) Because of this assumed radical break with heteronormativity, one key argument in the queer literature is that transgender bodiesdespite being a small minorityhold significant transgressive and political potential and therefore can or should be used as a trope in the battle against the marginalization caused by gender binaries (Davis, 2008;Garber, 1992;Whittle, 2000). Theoretically, this disruption opens up an opportunity to undo or redo gender.…”
Section: Introductionmentioning
confidence: 99%
“…One sociological study of transgender people, for example, found that 92% of respondents typically presented themselves as a man or as a woman in public and hoped to appear as such, despite the fact that only 67% of respondents identified themselves in binary terms (as either a man, woman, male, or female) (E. C. Davis, 2009). Given the limitations on publicly available gender categories, trans people are engaged in creating coherence for both themselves and others in situations where it may not be possible to convey the complexities of the gendered self or where it may be dangerous to do so (E. C. Davis, 2009). As such, the x marker functions to erase much that is disruptive about gender non-conformity, being its multiplicity and incoherence, by imposing norms of essentialism and stability.…”
Section: Legal Classificationmentioning
confidence: 99%